Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Inverse identification of wind turbine horizontal thrust on steel-concrete hybrid tower using intelligent algorithm - Shou-Zhen Li; Yu-Hang Wang; Jinjin Wang; Ran Deng; Chao Hu; Liming Jiang (Engineering Structures, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Molecular Mechanism of Absorption, Transport and Metabolic Transformation of Astaxanthin in Aquatic Animals - Huakang Peng; Yihui Du; Qianwen Ding; Dongdong Du; Ruyue Dong; Chao Ran; Zhen Zhang; Yuanyuan Yao; Hui Liang; Ming Li; Nan Wang; Yalin Yang; et al. (Reviews in Aquaculture, 2026)
The global astaxanthin market reached $1.69 billion in 2024, with 47% directed to aquafeed—yet the molecular basis of its absorption, metabolism, deposition, and storage in aquatic organisms remains incompletely resolved. A deeper understanding of these mechanisms will help optimize feed formulations, enhance astaxanthin bioavailability, and improve economic efficiency in aquaculture. This study investigates the absorption mechanisms of astaxanthin mediated by intestinal lipid transporters (SR‐B1, CD36, NPC1L1) and its utilization/deposition in different tissues and organs. It reviews the latest research progress on major absorption pathways, metabolic processes, and storage forms of astaxanthin in aquatic organisms, analyzes key factors affecting its utilization efficiency, and discusses potential future research directions to provide a scientific basis and theoretical support for aquaculture practices.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

C10–C12 aromatics dominate ozone and secondary organic aerosol formation potential in emissions from printed circuit board manufacturing - Xiaodie Pang; Wei Song; Weiqiang Yang; Chao Peng; Jianqiang Zeng; Zhou Zhang; Xiao Tian; Hongcheng Lu; Xiangyu Zhang; Ran An; Yang Li; Runcheng Zhu; et al. (Journal of Environmental Sciences, 2026)

Improving the accuracy of phase distribution measurement with ERT in multiphase flows by correcting fringe-effect artifacts - Ran Pang; Chao Wang; Xiao Liang; Jiamin Ye (Chemical Engineering Journal, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Relationships between sludge metabolic activity and the degree of extracellular polymeric substance stripping - Xianbao Wang; Xiyu Liu; Jiarong Ran; Baisha Song; Jinlei Cheng; Tiantian Chen; Anlong Zhang; Chao Zhu; Pengkang Jin (ENGINEERING Environment, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Levels and emission factors of polycyclic aromatic hydrocarbons in night market cooking fumes - Thi-Hieu Le; Cindy Soo Yun Tan; Hsin-Chieh Kung; Riza P. Gumaling; Danielle E. Que; How-Ran Chao; Ying I. Tsai; Xuan-Thanh Bui; Guo-Ping Chang-Chien; Lin-Chi Wang (Atmospheric Environment, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Porous MXene nanoplatform with ultrahigh drug loading for synergistic photothermal/photodynamic therapy and drug resistance reversal in osteosarcoma - Zhen Song; Ran-Ran Zhang; Zi-Chao Yan; Jie Wang; Youchang Liu; Chang-Qing Jiang; Meng Qiu; Bing-Xin Zheng; Bin Yue (Chemical Engineering Journal, 2026)

An improved ion-exchange-to-silver-salt procedure for δ18O measurement of nitrate in natural samples - Bo Wang; Chao Li; Ying Wang; Linbao Chen; Yuting Wang; Ran Ma; Zhengyu Zhu; Youping Zhou (Analytica Chimica Acta, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Tensile-compressive hysteresis performance of prestressed CFDST columns for offshore wind turbine structures - Kai-Yuan Jin; Xu-Hong Zhou; Chao Hu; Kang Wang; Yu-Hang Wang; Hao-Ran Xu (Ocean Engineering, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Moderate-intensity aerobic exercise inhibits cell pyroptosis to improve myocardial ischemia-reperfusion injury - Yu Wang; Yushan Li; Chaofan Chen; Hailong Zhang; Weili Liu; Chao Wu; Haonan Chen; Ran Li; Jinghan Wang; Yingchao Shi; Shengfang Wang; Chuanyu Gao (Molecular Biology Reports, 2025)

IGFBP7 and CCT2 are novel lactylation-driven mediators of endothelial-to-mesenchymal transition in idiopathic pulmonary fibrosis - Li Wenhao; Huang Ling; Fang Wanqing; Wang Wanrong; Cao Chao; Wang Ran (Functional & Integrative Genomics, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A highly fractionated origin for the Yanshanian water-rich A-type granite in the Southern Great Xing’an Range, NE China: Insights from zircon and monazite geochemistry - Zi-Yi Wang; Hao Yang; Hao-Ran Wu; Zhi-Chao Zhang; Zheng Ji; Yu Dong; Wen-Chun Ge (Journal of Asian Earth Sciences, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Micropropagation of Amygdalus pedunculata, an industrial shrub - Xiang-dong Bai; Ri-han Wu; Bai-chao Liu; Si-ran Wang; Yu-E Bai (South African Journal of Botany, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Novel carbonylomics with stable isotope-coded derivatization for non-targeted analysis of reactive carbonyl species in cooking oils - Chiung-Wen Hu; Yuan-Jhe Chang; Yi-Jhen Wang; Yet-Ran Chen; Marcus S. Cooke; Mu-Rong Chao (Journal of Hazardous Materials, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

The cell death-inducing protein BcPlp1 from Botrytis cinerea contributes to pathogenicity and modulates plant resistance - Xiaofei Nie; Ziyao Wang; Binbin Huang; Qiongnan Gu; Ran Xu; Shuang Yu; Chao Xiong; Zhiguo Liu; Wei Wei; Kai Bi; Wenjun Zhu (Plant Science, 2025)

Predicting Persistent Aneurysm Filling After Pipeline Embolization Device Treatment in Patients with Intracranial Aneurysm: Development and External Validation of a Nomogram Model - Linggen Dong; Chao Wang; Xiheng Chen; Mingtao Li; Tong Li; He Liu; Yang Zhao; Ran Duan; Weitao Jin; Yukun Zhang; Yang Wang; Ming Lv (Translational Stroke Research, 2025)

Quantitatively tracing the decomposition of endogenous particulate organic carbon during sinking in (sub-)deep reservoirs: Using radiocarbon isotopes Δ14C - Chao Yin; Yan Zeng; Jingan Chen; Guangrong Ran; Haiquan Yang; Jia Yu; Jingfu Wang; Ziyan Zhang; Xudong Guo (Water Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Surface-complexation-directed selective oxidation of phosphonates by decoration of copper anchoring sites - Hao Wang; Zixuan Zeng; Ran Duan; Hua Sheng; Chao Shan; Wenjing Song; Jincai Zhao (Chemical Engineering Journal, 2025)

Yeast cell wall extract as a strategy to mitigate the effects of aflatoxin B1 and deoxynivalenol on liver and intestinal health, and gut microbiota of largemouth bass (Micropterus salmoides) - Zhe Yu; Zhen Zhang; Tsegay Teame; Leluo Guan; Ruiguo Wang; Ronghua Zhu; Qingshuang Zhang; Hongwei Yang; Na Cui; Yuan Huang; Chao Ran; Yalin Yang; et al. (Aquaculture, 2025)

Experimental and numerical investigations on fluid resonance in moonpool affected by the side wall reflection - Hao Liu; Sheng-Chao Jiang; Ya-Qing Ran; Zi-Hao Wang; Zhi-Wei Song (Ocean Engineering, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

A geographically weighted neural network model for digital soil mapping of heavy metal copper in coastal cities - Yun Zeng; Tiezhu Shi; Qian Liu; Chao Yang; Zihong Zhang; Ran Wang (Journal of Hazardous Materials, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Cost-Effective multifunctional bilayer structural hydrogel evaporator for stable solar desalination and wastewater treatment - Xin-Yu Zhou; Shu-Chao Song; Wen-Xiu Wang; Hui-Ran Jin; Shan Yun; Ai-Bin Huang; Jing Chen (Chemical Engineering Journal, 2024)

Analyzing performance and microbial mechanisms in an incineration leachate treatment after waste separation: Integrated metagenomic and metaproteomic analyses - Han Wang; Xiaoqian Ma; Xiaochuan Ran; Tong Wang; Mingda Zhou; Chao Liu; Xiang Li; Min Wu; Yayi Wang (Science of The Total Environment, 2024)

Fabrication of zein/modified cyclodextrin nanofibers for the stability enhancement and delivery of curcumin - Yao Hu; Nicholas H. Rees; Chao Qiu; Jinpeng Wang; Zhengyu Jin; Ran Wang; Yinhua Zhu; Han Chen; Pengjie Wang; Siyuan Liu; Fazheng Ren; Gareth R. Williams (Food Hydrocolloids, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Novel visible-light activated photocatalytic ultrafiltration membrane for simultaneous separation and degradation of emerging contaminants - Ran Li; Zhidong Wei; Peng Li; Yangbo Qiu; Chengyi Wang; Chao Wang; Long-Fei Ren; Jiahui Shao; Yiliang He (Journal of Hazardous Materials, 2024)

Efficient and low-energy degradation of chlorobenzene via catA-mediated cleavage and bedC1 docking in a novel Burkholderia stabilis TF-2 - Zhilin Xing; Fang Gou; Xiaoping Zhang; Yanhui Gao; Xihong Ke; Dongni Ran; Peng Wang; Jiangfeng Guo; Heng Wu; Chao Peng; Tiantao Zhao (Chemosphere, 2024)

Quantification of two-phase flow in a microchannel heat exchanger header based on capacitance measurement - Jiajia Song; Hequn Liu; Chao Yuan; Ran Wang; Jinqing Peng; Lizhi Wang; Haobo Jiang; Houpei Li (International Journal of Refrigeration, 2024)

Undervalued dry riverbeds: A key factor in equating intermittent river CO2 emissions to perennial rivers - Chao Qin; Yuan Xue; Mengzhen Xu; Lishan Ran; Dongfeng Li; Ge Wang; Defan Cun; Baosheng Wu; Xudong Fu; Guangqian Wang (Water Research, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Novel electrocatalytic capacitive deionization with catalytic electrodes for selective phosphonate degradation: Performance and mechanism - Chengyi Wang; Siyue Xue; Yubo Xu; Ran Li; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Water Research, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Enhancing anaerobic digestion of actual papermaking wastewater with addition of Fenton sludge - Xianbao Wang; Xiang Li; Yili Xie; Jialu Zhang; Jiarong Ran; Minting Zhang; Lixin Zhang; Anlong Zhang; Chao Zhu (Journal of Water Process Engineering, 2024)

Dietary Bacillus velezensis T23 fermented products supplementation improves growth, hepatopancreas and intestine health of Litopenaeus vannamei - Hongwei Yang; Dongdong Du; Qingshuang Zhang; Tsegay Teame; Anran Wang; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Shengkang Li; et al. (Fish & Shellfish Immunology, 2024)

Revealing the comprehensive impact of organic compounds on the partial nitrification-anammox system during incineration leachate treatment: metabolic hierarchy and adaptation - Mingda Zhou; Junjie Wang; Han Wang; Xiaochuan Ran; Hao Xue; Chao Liu; Yayi Wang (Water Research, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Behavior of super-sized thin-walled CFDST columns for wind turbine towers subjected to combined loads: Experiment - Kai-Yuan Jin; Yu-Hang Wang; Xu-Hong Zhou; Ran Deng; Chao Hu; Hao Wen (Engineering Structures, 2024)

Gut bacterial community and gene expression alterations induced by transgenic Bt maize contribute to insecticidal activity against Mythimna separata - Chao Xu; Junyu Luo; Li Wang; Xiangzhen Zhu; Hui Xue; Ningbo Huangfu; Xueke Gao; Dongyang Li; Kaixin Zhang; Ran Chen; Jichao Ji; Changying Niu; et al. (Journal of Pest Science, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Effect of indigenous Saccharomyces cerevisiae strains on microbial community successions and volatile compounds changes during Longyan wine fermentation - Xiaodi Wang; Chao Dang; Yaqiong Liu; Xiaoxin Ge; Ran Suo; Qianyun Ma; Jie Wang (Food Bioscience, 2024)

Self-Assembled FeIII-TAML-Based Magnetic Nanostructures for Rapid and Sustainable Destruction of Bisphenol A - Ruochen Dong; Lihua Bai; Sijia Liang; Shuxia Xu; Song Gao; Hongjian Li; Ran Hong; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2024)

Effective electrosorption and recovery of phosphorus by capacitive deionization with a covalent organic framework-membrane coating electrode - Chengyi Wang; Ran Li; Yubo Xu; Zhongbao Ma; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Characterization of a fermented dairy, sour cream: Lipolysis and the release profile of flavor compounds - Meng-Song Wang; Min Fan; An-Ran Zheng; Chao-Kun Wei; Dun-Hua Liu; Kiran Thaku; Zhao-Jun Wei (Food Chemistry, 2023)

Quantifying the contribution of temperature, salinity, and climate change to sea level rise in the Pacific Ocean: 2005-2019 - Junlin Ran; Nengfang Chao; Lianzhe Yue; Gang Chen; Zhengtao Wang; Tangting Wu; Chengchun Li (Frontiers in Marine Science, 2023)
In recent decades, Pacific Ocean’s steric sea level anomaly (SSLA) has shown prominent patterns among global sea level variations. With ongoing global warming, the frequency and intensity of climate and sea level changes have increased, particularly in the tropical Pacific region. Therefore, it is crucial to comprehend the overall trends and mechanisms governing volumetric sea level changes in the Pacific. To accurately quantify the spatiotemporal evolution characteristics of density-driven sea level change in the Pacific Ocean (PO) from 2005 to 2019, we decomposed temperature and salinity into linear trends, interannual variations, seasonal variations, and residual terms using the STL (seasonal-trend decomposition based on loess) method. To evaluate the influence of ocean temperature, salinity, and climate change on density-driven sea level change and its underlying mechanisms, we decompose temperature as well as salinity changes through into the Heaving (vertical displacements of isopycnal surfaces) and Spicing (density-compensated temperature and salinity change) modes. The findings reveal an average steric sea level rise rate of 0.34 ± 0.16 mm/yr in the PO from 2005 to 2019. Thermosteric sea-level accounts for 82% of this rise, primarily due to seawater temperature rise at depths of 0-700 m caused by Heaving mode changes. Accelerated SSLA increase via the thermosteric effect has been connected to interactions between greater Ekman downwelling from surface winds, radiation forcing linked to global greenhouse gases, and changes in the Pacific warm currents triggered by El Niño-Southern Oscillation (ENSO) episodes. Although salinity is affected by the Subantarctic Mode Water (SAMW) and the Antarctic Intermediate Water (AAIW) in the southern Indian Ocean, however the significance of salinity in sea level change is little compared to the role played by thermocline shift. This study offers a substantial contribution to the field, providing robust data and technical support, and facilitating a deeper understanding of the mechanisms underlying the effects of temperature and salinity on sea level changes during periods of rapid climate change, thus enhancing the accuracy of future predictions regarding sea level rise.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Multi-omics analysis revealed NMBA induced esophageal carcinoma tumorigenesis via regulating PPARα signaling pathway - Hu Zhang; Chao Zhao; Ying Zhang; Lu Lu; Wei Shi; Qian Zhou; Yuepu Pu; Shizhi Wang; Ran Liu; Lihong Yin (Environmental Pollution, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Soil Carbon Emission Sources Differ Under Litter and Nutrient Addition During Secondary Succession: Evidence from a Mesocosm Study Using a Three-Transfer-Pool Model - Tiantian Li; Cuijuan Liao; Chao Wang; Weiming Yan; Ran Sun; Yangquanwei Zhong (Journal of Soil Science and Plant Nutrition, 2023)

Crystal-modeler: A tool for geometric analysis and three-dimensional modeling of crystal forms based on rectangular coordinates in space - Huixia Chao; Yue Li; Weihua Yao; Xin Han; Ran Wang (Earth Science Informatics, 2023)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Exogenous artificial DNA forms chromatin structure with active transcription in yeast - Jianting Zhou; Chao Zhang; Ran Wei; Mingzhe Han; Songduo Wang; Kaiguang Yang; Lihua Zhang; Weigang Chen; Mingzhang Wen; Cheng Li; Wei Tao; Ying-Jin Yuan (Science China Life Sciences, 2022)
Yeast artificial chromosomes (YACs) are important tools for sequencing, gene cloning, and transferring large quantities of genetic information. However, the structure and activity of YAC chromatin, as well as the unintended impacts of introducing foreign DNA sequences on DNA-associated biochemical events, have not been widely explored. Here, we showed that abundant genetic elements like TATA box and transcription factor-binding motifs occurred unintentionally in a previously reported data-carrying chromosome (dChr). In addition, we used state-of-the-art sequencing technologies to comprehensively profile the genetic, epigenetic, transcriptional, and proteomic characteristics of the exogenous dChr. We found that the data-carrying DNA formed active chromatin with high chromatin accessibility and H3K4 tri-methylation levels. The dChr also displayed highly pervasive transcriptional ability and transcribed hundreds of noncoding RNAs. The results demonstrated that exogenous artificial chromosomes formed chromatin structures and did not remain as naked or loose plasmids. A better understanding of the YAC chromatin nature will improve our ability to design better data-storage chromosomes.

The dysregulation of unsaturated fatty acid-based metabolomics in the MNNG-induced malignant transformation of Het-1A cells - Hu Zhang; Qiwei Liu; Chao Zhao; Ying Zhang; Shizhi Wang; Ran Liu; Yuepu Pu; Lihong Yin (Environmental Science and Pollution Research, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Molecular cloning and characterization of angiopoietin-like protein-8 gene in pigs and its tissue-specific expression in different animals - Chao-Ran Wang; Hong-Bo Xiao; Xiang-Yang Lu; Fu-Shen Huang (Biologia, 2021)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Multipath mitigation in GNSS precise point positioning based on trend-surface analysis and multipath hemispherical map - Ran Lu; Wen Chen; Danan Dong; Zhiren Wang; Chenglong Zhang; Yu Peng; Chao Yu (GPS Solutions, 2021)

Medial Preoptic Area Modulates Courtship Ultrasonic Vocalization in Adult Male Mice - Shu-Chen Gao; Yi-Chao Wei; Shao-Ran Wang; Xiao-Hong Xu (Neuroscience Bulletin, 2019)

Characterizing differences in microbial community composition and function between Fusarium wilt diseased and healthy soils under watermelon cultivation - Tingting Wang; Yuewen Hao; Mingzhu Zhu; Sitian Yu; Wei Ran; Chao Xue; Ning Ling; Qirong Shen (Plant and Soil, 2019)

Effects of different green manure treatments on soil apparent N and P balance under a 34-year double-rice cropping system - Xi Hong; Chao Ma; Jusheng Gao; Shiming Su; Tao Li; Zunchang Luo; Ran Duan; Yanan Wang; Lingyu Bai; Xibai Zeng (Journal of Soils and Sediments, 2019)

Effect of LSU and ITS genetic markers and reference databases on analyses of fungal communities - Chao Xue; Yuewen Hao; Xiaowei Pu; C. Ryan Penton; Qiong Wang; Mengxin Zhao; Bangzhou Zhang; Wei Ran; Qiwei Huang; Qirong Shen; James M. Tiedje (Biology and Fertility of Soils, 2019)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Progress in fish gastrointestinal microbiota research - An R. Wang; Chao Ran; Einar Ringø; Zhi G. Zhou (Reviews in Aquaculture, 2018)
The gastrointestinal (GI) microbiota of vertebrates plays critical roles in nutrition, development, immunity and resistance against invasive pathogens. In the past decade, research of the GI microbiota of mammals has drastically increased our knowledge on the microbiota and their relationship with health and disease. However, our understanding of fish intestinal microbiota is limited. This review provides an overview of research on fish gut microbiota, including microbial composition, formation, factors that affect the GI microbes and characteristics of fish intestinal microbiota compared with human and mice. Further, the updated research on gnotobiotic zebrafish is elaborated and the insights gained on functions of the fish intestinal microbiota are discussed. Understanding the intestinal microbiota of fish will guide the development of probiotics, prebiotics and hopefully probiotic effectors as novel additives to improve the health of fish.

Correction to: In Vitro-In Vivo Dose Response of Ursolic Acid, Sulforaphane, PEITC, and Curcumin in Cancer Prevention - Christina N. Ramirez; Wenji Li; Chengyue Zhang; Renyi Wu; Shan Su; Chao Wang; Linbo Gao; Ran Yin; Ah-Ng Tony Kong (The AAPS Journal, 2018)

In Vitro-In Vivo Dose Response of Ursolic Acid, Sulforaphane, PEITC, and Curcumin in Cancer Prevention - Christina N. Ramirez; Wenji Li; Chengyue Zhang; Renyi Wu; Shan Su; Chao Wang; Linbo Gao; Ran Yin; Ah-Ng Kong (The AAPS Journal, 2018)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

Significant alteration of soil bacterial communities and organic carbon decomposition by different long‐term fertilization management conditions of extremely low‐productivity arable soil in S outh C hina - Weibing Xun; Jun Zhao; Chao Xue; Guishan Zhang; Wei Ran; Boren Wang; Qirong Shen; Ruifu Zhang (Environmental Microbiology, 2016)
Summary Different fertilization managements of red soil, a kind of Ferralic Cambisol, strongly affected the soil properties and associated microbial communities. The association of the soil microbial community and functionality with long‐term fertilization management in the unique low‐productivity red soil ecosystem is important for both soil microbial ecology and agricultural production. Here, 454 pyrosequencing analysis of 16S recombinant ribonucleic acid genes and GeoC hip4‐NimbleGen‐based functional gene analysis were used to study the soil bacterial community composition and functional genes involved in soil organic carbon degradation. Long‐term nitrogen‐containing chemical fertilization‐induced soil acidification and fertility decline and significantly altered the soil bacterial community, whereas long‐term organic fertilization and fallow management improved the soil quality and maintained the bacterial diversity. Short‐term quicklime remediation of the acidified soils did not change the bacterial communities. Organic fertilization and fallow management supported eutrophic ecosystems, in which copiotrophic taxa increased in relative abundance and have a higher intensity of labile‐ C ‐degrading genes. However, long‐term nitrogen‐containing chemical fertilization treatments supported oligotrophic ecosystems, in which oligotrophic taxa increased in relative abundance and have a higher intensity of recalcitrant‐ C ‐degrading genes but a lower intensity of labile‐ C ‐degrading genes. Quicklime application increased the relative abundance of copiotrophic taxa and crop production, although these effects were utterly inadequate. This study provides insights into the interaction of soil bacterial communities, soil functionality and long‐term fertilization management in the red soil ecosystem; these insights are important for improving the fertility of unique low‐productivity red soil.

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Depositional environment and micropore characteristics of the Ediacaran Doushantuo Formation black shale in Western Hubei, China - Hao Wang; Ziquan Yong; Xuan Zhang; Bo Ran; Di Yang; Chao Luo; Bin Deng (Arabian Journal of Geosciences, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Wild soybean roots depend on specific transcription factors and oxidation reduction related genesin response to alkaline stress - Huizi DuanMu; Yang Wang; Xi Bai; Shufei Cheng; Michael K. Deyholos; Gane Ka-Shu Wong; Dan Li; Dan Zhu; Ran Li; Yang Yu; Lei Cao; Chao Chen; et al. (Functional & Integrative Genomics, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

A recombinant peroxisome proliferator response element-driven luciferase assay for evaluation of potential environmental obesogens - Ya-Fen Wang; How-Ran Chao; Chia-Hsin Wu; Chu-Han Tseng; Ya-Ting Kuo; Tsui-Chun Tsou (Biotechnology Letters, 2010)